2020
DOI: 10.3390/s20061630
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Uncertainty of a Laser Triangulator Considering System Covariances

Abstract: A laser triangulation system, which is composed of a camera and a laser, calculates distances between objects intersected by the laser plane. Even though there are commercial triangulation systems, developing a new system allows the design to be adapted to the needs, in addition to allowing dimensions or processing times to be optimized; however the disadvantage is that the real accuracy is not known. The aim of the research is to identify and discuss the relevance of the most significant error sources in lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A primary obstacle in this scenario was ensuring laser safety, given that the system operated in real-time with an optical power exceeding 5 mW of continuous power. A third and final solution, thoroughly investigated in this study, revolves around the utilization of an optical triangulator [ 12 , 13 , 14 , 15 , 16 ]. This approach strikes a delicate balance between complexity, cost, and performance.…”
Section: Laser Sensing Techniquementioning
confidence: 99%
“…A primary obstacle in this scenario was ensuring laser safety, given that the system operated in real-time with an optical power exceeding 5 mW of continuous power. A third and final solution, thoroughly investigated in this study, revolves around the utilization of an optical triangulator [ 12 , 13 , 14 , 15 , 16 ]. This approach strikes a delicate balance between complexity, cost, and performance.…”
Section: Laser Sensing Techniquementioning
confidence: 99%
“…It was found that the calibration process has been the main error source which contributed over 97% of the maximum error deflection. 30 Based on this condition, a calibration process is necessary for a precise measurement result. The traditional calibration usually requires precise movement or precise gauge, which needs a high extra cost.…”
Section: Light Deflectionmentioning
confidence: 99%
“…In 2020, Pablo Puerto et al analyzed the relevance of the main error sources in a laser system using the Monte Carlo method. It was found that the calibration process has been the main error source which contributed over 97% of the maximum error deflection 30 . Based on this condition, a calibration process is necessary for a precise measurement result.…”
Section: Laser Triangulation Measurementmentioning
confidence: 99%